France, story of a childhood - Rahmani, Zahia 1962- (Yale University Press, 2016)
An intimate, autobiographical novel of an alleged Harki Algerian family's exile from home and unwelcoming reception in France. A timely and moving tale of uprooting and resettlement, imprisonment and escape, persecution and loss, narrated by the daughter of an aleged Harki, and Algerian soldier who fought for the French during the Algerian War of Independence. It was the fate of such men to be twice exiled, first in their homeland after the war, and later in France, where fleeing Harki families sought refuge but instead faced contempt, discrimination, and exclusion. Sahia Rahmani blends reality and imagination in her writing, offering a fictionalized version of her own family's struggle. With ingenuity that defies categories and genre, the author delves deeply into her past with the immediacy of memoir, the reflection of essay, the artistry of fiction, and the relevance of reportage. From the unique perspective of the daughter of an accused Harki, she examines France's complex and controversial history with its former colony and offers new insight into the French civil riots of 2005. She makes a stirring plea for understanding between generations and cultures, and especially for an end to the destructive practice of condemning children for their fathers' actions and beliefs.